Binding of an X-Specific Condensin Correlates with a Reduction in Active Histone Modifications at Gene Regulatory Elements. Issue 3 (22nd May 2019) - Street, Lena Annika; Morao, Ana Karina; Winterkorn, Lara Heermans; Jiao, Chen-Yu; Albritton, Sarah Elizabeth; Sadic, Mohammed; Kramer, Maxwell; Ercan, Sevinç
Abstract: Condensins are evolutionarily conserved protein complexes that mediate chromosome compaction during cell division and have been implicated in gene regulation during interphase. Here, Street et al. analyzed the gene regulatory role of an X -specific... Condensins are evolutionarily conserved protein complexes that are required for chromosome segregation during cell division and genome organization during interphase. In Caenorhabditis elegans, a specialized condensin, which forms the core of the dosage compensation complex (DCC), binds to and represses X chromosome transcription. Here, we analyzed DCC localization and the effect of DCC depletion on histone modifications, transcription factor binding, and gene expression using chromatin immunoprecipitation sequencing and mRNA sequencing. Across the X, the DCC accumulates at accessible gene regulatory sites in active chromatin and not heterochromatin. The DCC is required for reducing the levels of activating histone modifications, including H3K4me3 and H3K27ac, but not repressive modification H3K9me3. In X -to-autosome fusion chromosomes, DCC spreading into the autosomal sequences locally reduces gene expression, thus establishing a direct link between DCC binding and repression. Together, our results indicate that DCC-mediated transcription repression is associated with a reduction in the activity of X chromosomal gene regulatory elements.